Doping effects on trimerization and magnetoelectric coupling of single crystal multiferroic (Y, Lu)MnO3. (27th January 2017) - Choi, Seongil; Sim, Hasung; Kang, Soonmin; Choi, Ki-Young; Park, Je-Geun
Abstract: Hexagonal RMnO3 is a multiferroic compound with a giant spin–lattice coupling at an antiferromagnetic transition temperature, Lee et al (2008 Nature 451 805). Despite extensive studies over the past two decades, the origin and underlying microscopic mechanism of strong spin–lattice coupling remain very much elusive. In this study, we have tried to address this problem by measuring the thermal expansion and dielectric constant of doped single crystals Y1− x Lu x MnO3 where x = 0, 0.25, 0.5, 0.75, and 1.0. From these measurements, we confirm that there is a progressive change in the physical properties with doping. At the same time, all our samples exhibit clear anomalies at T N, even in the samples where x = 0.5 and 0.75. This is opposed to some earlier ideas, which suggests an unusual doping dependence of the anomaly. Our work reveals yet another interesting facet of the spin–lattice coupling issue in hexagonal RMnO3 .